1999
DOI: 10.1038/44157
|View full text |Cite
|
Sign up to set email alerts
|

Signal relay by BMP antagonism controls the SHH/FGF4 feedback loop in vertebrate limb buds

Abstract: Outgrowth and patterning of the vertebrate limb are controlled by reciprocal interactions between the posterior mesenchyme (polarizing region) and a specialized ectodermal structure, the apical ectodermal ridge (AER). Sonic hedgehog (SHH) signalling by the polarizing region modulates fibroblast growth factor (FGF)4 signalling by the posterior AER, which in turn maintains the polarizing region (SHH/FGF4 feedback loop). Here we report that the secreted bone-morphogenetic-protein (BMP) antagonist Gremlin relays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(140 citation statements)
references
References 29 publications
7
131
0
2
Order By: Relevance
“…This shift is correlated with anterior expansion of the expression domain of Gli1, a transcriptional target of SHH signaling (8), and with a reduction in size of the Gli1-free anterior domain. Fgf8 expressing AER was narrower and its posterior domain was missing in Sall4 CKO hindlimb buds, which is consistent with the positive feedback loop between the ZPA and AER (29,30). Accordingly, expression of Fgf10, whose expression in developing limb buds is maintained by FGF8 signaling (26), exhibited a smaller expression domain (Fig.…”
Section: Sall4supporting
confidence: 58%
“…This shift is correlated with anterior expansion of the expression domain of Gli1, a transcriptional target of SHH signaling (8), and with a reduction in size of the Gli1-free anterior domain. Fgf8 expressing AER was narrower and its posterior domain was missing in Sall4 CKO hindlimb buds, which is consistent with the positive feedback loop between the ZPA and AER (29,30). Accordingly, expression of Fgf10, whose expression in developing limb buds is maintained by FGF8 signaling (26), exhibited a smaller expression domain (Fig.…”
Section: Sall4supporting
confidence: 58%
“…It has been shown that these signaling centers are interconnected, but the way they interact is not completely understood (Laufer et al, 1994;Niswander et al, 1994;Zú ñiga et al, 1999;Pizette et al, 2001). In addition, although various molecules mediating the action of the signaling centers have been identified and their signaling pathways elucidated, many components are still missing (Capdevilla and Izpisú aBelmonte, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the tetrapod limb bud, tempered activity of Bone Morphogenetic Protein (Bmp) family members by BMP antagonists is crucial in maintaining feedback between the zone of polarizing activity and the apical ectodermal ridge. BMP signaling negatively regulates limb bud outgrowth by promoting apical ectodermal ridge regression (30,31), and this effect is counteracted by Shh-dependent expression of the secreted BMP antagonist Gremlin (32,33). A similar role for antagonist-modulated BMP signaling has been demonstrated in the developing mammalian genital tubercle (34).…”
Section: Discussionmentioning
confidence: 83%